2015
DOI: 10.1039/c4tb01823k
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanofiber–titania nanocomposites as potential drug delivery systems for dermal applications

Abstract: Nanocomposites with potential for dermal drug delivery have been developed using nanotitania chemically grafted onto nanocellulose as an active ingredient for enhanced uptake and controlled release of model drug loads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 60 publications
2
58
0
1
Order By: Relevance
“…Possible explanation for this observation can be attributed to the poor solubility of TC and as a result, its limited diffusion in MH agar. These results were in good agreement with release kinetics of ATP studies 17 and clearly demonstrated that the usage of titania provides much slower release of Phos. 33 In contrast, the too slow release of Phos from nanocomposites with titania (CNF_TiO 2 _Phos_M2) did not permit the drug to achieve a concentration high enough to inhibit bacteria growth, rendering the related nanocomposite formulations inactive.…”
Section: View Article Onlinesupporting
confidence: 83%
See 4 more Smart Citations
“…Possible explanation for this observation can be attributed to the poor solubility of TC and as a result, its limited diffusion in MH agar. These results were in good agreement with release kinetics of ATP studies 17 and clearly demonstrated that the usage of titania provides much slower release of Phos. 33 In contrast, the too slow release of Phos from nanocomposites with titania (CNF_TiO 2 _Phos_M2) did not permit the drug to achieve a concentration high enough to inhibit bacteria growth, rendering the related nanocomposite formulations inactive.…”
Section: View Article Onlinesupporting
confidence: 83%
“…No new absorption peaks after Phos modification were observed for CNF_TiO 2 _Phos_M2 17 (see also Fig. The spectrum revealed a well-defined maximum at 310 nm -a distinct shift to shorter wavelengths compared to the derivatives of carboxylic acids (375 nm for the surface complex with Diclophenac and 474 nm for that with the D Penicillamine), 17 indicating relatively stronger bonding to the phosphonate ligand. For this reason, we confirmed the formation of a chelating complex between titania and drug molecules by UV-Vis spectroscopy (please, see Fig.…”
Section: Characterization Of Tio 2 -Nanocellulose Nanocomposites Lmentioning
confidence: 90%
See 3 more Smart Citations